Pengaruh Metode Diskusi dengan Alat Peraga Papan Berpaku terhadap Hasil Belajar Matematika Siswa - Hamzah Upu; Ilham Minggi; Isnaeni Sari (Issues in Mathematics Education (IMED), 2019)
This research aimed to determine wheter there was the influence of discussion method with geoboard teaching aids to students’ mathematics learning achievement. The type of this research was a quasi-experiment involving two groups with different treatment. The population of this research was students of grade VII and selected two classes by cluster random sampling as the research sample, that were class VII-4 and VII-5. The results obtained that: (1) students’ mathematics learning achihevement who were being taught by using discussion method with geoboard teaching aids is higher than the students’ mathematics learning achievement who were being taught by using discussion method. (2) The improvement of students’ mathematics learning achievement who were being taught by using discussion method with geoboard teaching aids is higher than the improvement of students’ mathematics learning achievement who were being taught by using discussion method. From the results of this research, it can be conclude that there is influence of discussion methods with geoboard teaching aids to students’ mathematics learning achievement.